Predicting the adult heights of female athletes: Talent identification for world-class synchronized swimmers - Homma, M.; Ito, K.; Sasahara, C. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
This study aims to examine a program to predict the heights of Japanese women that will be useful when finding tall athletes. The height record data from birth until the mature height was collected for 45 synchronized swimmers and 34 female university students who were 163 cm tall or more. The groups` mature heights and the height values and growth velocity curve parameters predicted were analyzed using the BTT model. The growth velocity curve parameters for both groups had the same level of values, and there was no statistically significant difference observed. There were no large differences observed in the growth velocity curve parameters of prior research that targeted non-athletes healthy women and the parameters of the target group. Accordingly, synchronized swimmers can be considered to have the same growth patterns as non-athletes healthy women. A correlation was found between the predicted height values and people`s mature heights. However, in cases a person`s mature height was 160 cm or more, the predicted height tended to be underestimated, and in cases a person`s mature height was 160 cm or less, the predicted height tended to be overestimated. The accuracy seems to increase by simultaneously using assessments based on other data, such as the characteristics of the growth velocity curve parameters and the height of parents. In addition, it was suggested that an early age of puberty-related growth spurt and a fast growth rate at the onset of puberty are important factors to Identify predicted tall female athletes.